A Case against the Categorisation of Children and Youth Part 1: Theoretical perspectives. (Kairaranga, 2006)
This is the first of two articles that provide a critique of categorisation and of the biomedical interpretation of personal adjustment issues experienced by children and youth. In this paper the appraisal is made by the devising of an imaginary mental illness, through the presentation of some important theoretical frameworks, by considering contributions from contemporary developmental psychology, and through a brief linguistic, historical and policy analysis. These viewpoints are severely critical, both individually and collectively, of categorisation and the medical model. The critique is further strengthened by a professional practice perspective that will be published in Kairaranga in September.